2021
DOI: 10.3233/wor-203358
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors that influenced wellbeing and learning effectiveness during the sudden transition into eLearning due to the COVID-19 lockdown

Abstract: BACKGROUND: The sanitary emergency due to COVID-19 virus obliged people to face up several changes in their everyday life becauseWorld Health Organisation (WHO) guidelines and countries' Health Systems imposed lockdown of activities and social distancing to flatten the infection curve. One of these rapid changes involved students and professors that had to turn the traditional "in presence" classes into online courses facing several problems for educational delivery. OBJECTIVES: This work aimed to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 53 publications
0
23
0
3
Order By: Relevance
“…The development of distance education is a topic of common concern for many scholars. The outbreak of the epidemic has promoted the development of digital classrooms to a certain extent ( Chauhan et al, 2021 ; Naddeo et al, 2021 ). On the contrary, developing countries represented by India are more concerned about the economic sustainability of the epidemic, such as energy consumption ( Su and Urban, 2021 ; Wang and Han, 2021 ), financial markets ( Youssef et al, 2021 ), etc.…”
Section: Resultsmentioning
confidence: 99%
“…The development of distance education is a topic of common concern for many scholars. The outbreak of the epidemic has promoted the development of digital classrooms to a certain extent ( Chauhan et al, 2021 ; Naddeo et al, 2021 ). On the contrary, developing countries represented by India are more concerned about the economic sustainability of the epidemic, such as energy consumption ( Su and Urban, 2021 ; Wang and Han, 2021 ), financial markets ( Youssef et al, 2021 ), etc.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that e-learning widened the gap between different socioeconomic groups in terms of accessibility to e-learning. In developing countries, the lack of computers, smartphones, digital infrastructure, low digital literacy, and electricity were important challenges facing the application of elearning [54][55][56]. However, it is essential to highlight the opportunities to address these issues moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…This could contribute to students' negative perceptions of e-learning. Additionally, the affective component represented by the presence of the teacher and colleagues may be an important learning factor during face-to-face activities [20,21]. Future studies are essential to better comprehend these data.…”
Section: Discussionmentioning
confidence: 99%